Dehydrogenative ester synthesis from enol ethers and water with a ruthenium complex catalyzing two reactions in synergy. Issue 4 (10th February 2022) - Kar, Sayan; Luo, Jie; Rauch, Michael; Diskin-Posner, Yael; Ben-David, Yehoshoa; Milstein, David
Abstract : We report the dehydrogenative synthesis of esters via enol ether oxidation, using water as the formal oxidant, catalyzed by a newly developed ruthenium acridine-based PNP(Ph)-type complex. Abstract : We report the dehydrogenative synthesis of esters from enol ethers using water as the formal oxidant, catalyzed by a newly developed ruthenium acridine-based PNP(Ph)-type complex. Mechanistic experiments and density functional theory (DFT) studies suggest that an inner-sphere stepwise coupled reaction pathway is operational instead of a more intuitive outer-sphere tandem hydration–dehydrogenation pathway.